Mrs Upaya Hukum Konsumen atas Wanprestasi dalam Jasa Titip Barang Impor Online: Tinjauan Hukum Perdata dan Fiqh Islam : A Comparative Normative Study of Civil and Islamic Legal Perspectives - Windiarti, Wulan; Paramita, Itsma (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The development of digital technology has given rise to the practice of online consignment services for imported goods, which makes it easier for consumers to obtain products from abroad. However, at the same time, it has also given rise to legal problems when service providers do not fulfill their obligations as agreed, such as late delivery, mismatched goods, or no delivery of goods at all. This study aims to analyze the forms of breach of contract and legal liability of online jastip service providers and to examine the legal protection mechanisms for consumers from the perspective of Indonesian civil law and Islamic jurisprudence. The research method used is normative juridical with a legislative and conceptual approach through analysis of the provisions of the Civil Code (KUHPerdata), Law Number 8 of 1999 concerning Consumer Protection, and muamalah fiqh literature regarding wakalah bil ujrah contracts. The results of the study show that in civil law, default in a jastip agreement gives consumers the right to demand fulfillment, contract cancellation, and compensation as stipulated in Articles 1233 and 1243 of the Civil Code and the Consumer Protection Law. From the perspective of Islamic jurisprudence, jastip is categorized as a wakalah bil ujrah contract that requires the principles of trust, transparency, and clarity of contract, so that when a breach of contract occurs without a valid excuse, the service provider is obliged to bear the losses (dhaman) both morally and legally. This study confirms the common ground between Indonesian civil law and Islamic jurisprudence in placing legal responsibility on business actors to protect consumer rights. Despite the existence of a clear legal basis, the practice of online proxy shopping still requires more stringent specific regulations and adequate legal education for consumers so that they can understand, demand, and effectively defend their rights in cross-border digital transactions.